The impact of the COVID-19 pandemic on bank lending: A sectoral analysis - Stephanie Kimani (Kenya Bankers Association (KBA), 2023)
This study examined the impact of the COVID-19 pandemic on bank lending across various sectors in Kenya. Using a multivariate Vector Autoregressive (VAR) model within a time series data framework, the study established the existence of both direct and indirect COVID induced shocks on credit allocation to various sectors in the Kenyan economy. The main finding of the study was that the credit allocation response to the COVID-19 pandemic was through the demand channel. Therefore, any policy aimed at minimizing pandemicinduced economic damage by stimulating demand was not sufficient in catering for emerging supply distortions. Additionally, given that the COVID-19 pandemic induced uncertainty, resulting in a lagged response as revealed by the IRFs, most commercial banks would require to be incentivized, through prudential and supervisory bank regulations to extend and sustain positive credit allocation to the private sector.
Keywords: 330